A crítica à Psicologia Científica e a sua renovação: encontros da Fenomenologia Transcendental de Edmund Husserl e da Psicologia Transcendente de Farias Brito - Rezende, Gabriel Fonseca (2021)
The objective of this research is to present the encounters and disagreements between the thoughts of Edmund Husserl and the Brazilian philosopher Raimundo de Farias Brito that permeate the philosophical criticisms in relation to Positivism and Scientific Psychology and, from this, how they developed an authentic Psychology with similarities. Both philosophers made a diagnosis of the crisis of Science, which affects Scientific Psychology, and presented a project for overcoming the crisis and renewal of culture. Husserl reflected that the crisis of the sciences consists of a European humanity that has lost belief in the capacity of reason to provide satisfactory answers to the basic problems of human existence, replacing knowledge with technique. Farias Brito reflected the establishment of a darkness over Western thought due to materialist positivism and skeptical criticism. The meaning of this darkness is the exclusion of the reality of the spirit, in the name of the positive given and the reduction of the real to the material. The purpose of this research is, therefore, to explore the possible relationships between the two philosophies regarding their criticisms to Scientific Psychology and their proposals for the refoundation of Psychology. It was sought to understand the scenario of scientific production on the theme through bibliographic reviews. From that, two articles were produced to be presented here. The first is called “Crisis in Science and in Psychology: the critiques of Edmund Husserl and Farias Brito”, whose objective consisted of highlighting the so-called "crisis" of science and humanity, arising from positivism-naturalism, and the so-called "crisis" of psychological science, as denounced by Edmund Husserl and Farias Brito, as well as the criticisms of both to Scientific Psychology. The second article, on the other hand, is entitled “The crisis of Psychology and its Restoration: proposals for overcoming it and the links between Edmund Husserl's Phenomenology and Farias Brito's Transcendent Psychology”. This article aimed (i) to reconstitute the elaboration of a new Psychology in both philosophers, as a possibility for the renewal of science through philosophy; (ii) explain, specifically in the question of psychological science, possible conceptual encounters and disagreements between the philosophies of these philosophers; and, finally, (iii) analyze the reasons for the similarities. The results showed that Many convergences between Husserl’s and Brito’s thinking were found, regarding the comprehension of the human soul, even though they had no contact with each other. Both denounced the misconception of the direct transposition of the positive method to Psychology, making it impossible to have access to psychological essences, to the study of human totality, and to the answers for essential human issues. Such similarities were already catalogued in literature and it was also possible to assert others, through elaboration's reconstitution of both of the new Psychology - Phenomenologic Psychology of Husserl and Transcendent Psychology of Farias Brito. This new Psychology has no more basis with materialism's parameters. Evident differences between both Psychologies were observed as well. At last, it was concluded that one of the possible reasons for their similarities lies in motivation - long lasting goals - that guided them. New research may point out new parallelism, new divergences and new reasons for their convergences.